Comparison of Nutrient Recommendations for Broilers - Yan, F.; Coto, C.; Wang, Z.; Cerrate, S.; Watkins, S.E.; Waldroup , P.W. (International Journal of Poultry Science, 2010)
Various recommendations exist for formulating broiler diets. In this study, diet specifications were compared for four different scenarios which included U.S. Poultry Industry average, recommendations by two major breeders and Brazilian recommendations. For each of these, amino acid specifications were adjusted to a percent per Mcal basis as the various recommendations utilize different energy levels. Performance of birds formulated to different nutrient recommendations varied depending primarily upon the relative levels of crude protein, amino acids and metabolizable energy. Feeding diets higher in crude protein and amino acids tended to result in faster growth, especially in early stages, but were less efficient in conversion of crude protein and amino acids into body weight gain. Feeding diets higher in metabolizable energy tended to result in better feed conversion, however effects of dietary energy on calorie conversion were somewhat variable. Over the entire 49 d feeding period there were no significant differences among the various treatments for caloric efficiency. No economic analysis was made of the present study, as relative costs of energy and amino acids vary over time. However it is obvious that when protein costs are high relative to energy, feeding systems which recommend lower protein and amino acid levels should be more economical, while perhaps resulting in a small sacrifice in body weight gain, while feeding systems that recommend higher protein and amino acid levels might be more economical when protein is relatively lower in comparison to dietary energy costs. Because overall calorie utilization was similar among nutrient programs at the conclusion of the study, this could be used as an overall indication of economic efficiency when comparing the different nutrient programs.